2018
DOI: 10.1002/cctc.201701899
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effective Palladium‐Doped Cu Bimetallic Materials to Tune Selectivity and Activity by using Doped Atom Ensembles as Active Sites for Efficient Removal of Acetylene from Ethylene

Abstract: The catalytic activity and selectivity of cost‐effective noble‐metal‐doped common metal materials strongly depend on the doped atom ensemble in specific arrangements to provide active sites. In this study, aiming at insight into the doped atom ensembles as active sites for tuning the selectivity and activity towards the target reaction, different doped noble metal Pd atom ensembles for cost‐effective Pd‐doped Cu catalysts act as active sites to investigate the activity and selectivity towards the efficient rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…As alternative nonprecious metal catalysts, Ni, Cu, Fe, alloys, intermetallic compounds (Ni 3 Ga, Ni 3 Sn 2 , and Al 13 Fe 4 ), and metal oxides (CeO 2 ) , have been investigated for selective hydrogenation of acetylene. Among them, Cu-based catalysts show excellent selectivity toward ethylene in the selective hydrogenation of acetylene, which is verified both experimentally and theoretically. , However, Cu is less active to dissociate hydrogen than precious metals, and the Cu-catalyzed selective hydrogenation of acetylene generally takes place at higher temperatures, which frequently results in fast deactivation because of fouling by the unwanted oligomers (also known as green oil) . To lower the reaction temperature, Kyriakou et al constructed a highly active and selective hydrogenation catalyst by isolating Pd atoms deposited on the Cu surface .…”
Section: Introductionmentioning
confidence: 99%
“…As alternative nonprecious metal catalysts, Ni, Cu, Fe, alloys, intermetallic compounds (Ni 3 Ga, Ni 3 Sn 2 , and Al 13 Fe 4 ), and metal oxides (CeO 2 ) , have been investigated for selective hydrogenation of acetylene. Among them, Cu-based catalysts show excellent selectivity toward ethylene in the selective hydrogenation of acetylene, which is verified both experimentally and theoretically. , However, Cu is less active to dissociate hydrogen than precious metals, and the Cu-catalyzed selective hydrogenation of acetylene generally takes place at higher temperatures, which frequently results in fast deactivation because of fouling by the unwanted oligomers (also known as green oil) . To lower the reaction temperature, Kyriakou et al constructed a highly active and selective hydrogenation catalyst by isolating Pd atoms deposited on the Cu surface .…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, some of them showed higher selectivity to ethylene than the Pd-based catalysts. For example, a high alkene selectivity is readily achieved in alkyne hydrogenation over Cu-based catalysts. Nevertheless, higher reaction temperatures (>150 °C) are often required because of the lower ability of hydrogen dissociation for the base-metal catalysts. A high reaction temperature often leads to enhanced oligomerization of acetylene, and the produced green oil fouls the catalyst surface and deactivates the catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous studies ,, have demonstrated that the higher temperature and H 2 /C 2 H 2 ratio can inhibit the formation of green oil, which will block the active site and result in the deactivation of the catalyst. Meanwhile, C 2 H 2 selective hydrogenation over M@Cu catalysts is examined in this study, and only on the higher temperature (>473 K), metal Cu can act as the active component in C 2 H 2 selective hydrogenation and exhibit high C 2 H 4 selectivity. , Moreover, the present study will carry out the comparisons between M@Pd (M = Au, Ag, and Cu) and M@Cu (M = Au, Ag, and Pd) core–shell catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the number of low-coordinated sites increased significantly with the decrease in particle size, such as the M 13 and M 38 clusters, which cannot be properly reflected using the periodic slab models. Moreover, our previous studies about C 2 H 2 selective hydrogenation over the Pd-doped Cu bimetallic catalyst used the periodic slab model to simulate the core–shell Pd-doped Cu catalyst with the outermost layer Cu atoms of the periodic Cu(111) surface replaced by Pd atoms, which exhibits poor C 2 H 4 selectivity; namely, the calculated results using the periodic slab model are not consistent with the experimental results that the Pd-doped Cu bimetallic catalyst significantly improve C 2 H 4 selectivity. However, our results using the cluster model in this study show that the Pd-doped Cu bimetallic catalyst exhibits excellent C 2 H 4 selectivity and activity.…”
Section: Calculation Methods and Modelsmentioning
confidence: 99%